Handbook on Effective Prosecution Responses to Violence against Women and Girls - United Nations Office on Drugs; Crime (United Nations, 2015)
Prosecutors play a critical role in the criminal justice response to violence against women and girls. Prosecuting gender based violent crime can be challenging. Often there are a number of challenges, due to the private nature of the offence, and police investigation may be substandard. Victims may be uncooperative, withdraw or recant their complaints. Judges or juries may employ gender bias or common myths surrounding violence against women and girls when examining the credibility of the victim and the facts of the case. Drawing upon the updated Model Strategies and Practical Measures on the Elimination of Violence against Women in the Field of Crime Prevention and Criminal Justice (General Assembly resolution 65/228, annex), UNODC and UN Women have drafted the Handbook on Effective Prosecution Responses to Violence against Women and Girls. Recognizing that prosecutors work in different legal systems, it is meant to be a helpful resource for individual prosecutors and prosecution services.